2012
DOI: 10.3109/17435390.2012.729274
|View full text |Cite
|
Sign up to set email alerts
|

Combination of small size and carboxyl functionalisation causes cytotoxicity of short carbon nanotubes

Abstract: The use of carbon nanotubes (CNTs) could improve medical diagnosis and treatment provided they show no adverse effects in the organism. In this study, short CNTs with different diameters with and without carboxyl surface functionalisation were assessed. After physicochemical characterisation, cytotoxicity in phagocytic and non-phagocytic cells was determined. The role of oxidative stress was evaluated according to the intracellular glutathione levels and protection by N-acetyl cysteine (NAC). In addition to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 81 publications
2
28
1
Order By: Relevance
“…While several studies indicated that COOH functionalization significantly decreased CNT bioactivities, e.g. fibrogenic responses and pulmonary inflammation49505152, we and some others observed an increase in cytogenic, genotoxic and fibrogenic activities by COOH functionalization5354. In the present study, f-MWCNT elicited more robust effects on CAF-like cells and CSCs as compared to MWCNT.…”
Section: Discussioncontrasting
confidence: 53%
“…While several studies indicated that COOH functionalization significantly decreased CNT bioactivities, e.g. fibrogenic responses and pulmonary inflammation49505152, we and some others observed an increase in cytogenic, genotoxic and fibrogenic activities by COOH functionalization5354. In the present study, f-MWCNT elicited more robust effects on CAF-like cells and CSCs as compared to MWCNT.…”
Section: Discussioncontrasting
confidence: 53%
“…2012). Thinner CNTs were also found to be more cytotoxic to EAhy926, A549, HepG2, DMBM-2 V79 and TK-6 cells than thicker CNTs (Frohlich et al 2013). However, long and thick CNTs, but not short and thin MWCNTs, were shown to cause inflammation in mice (Yamashita et al 2010).…”
Section: Role Of Physico-chemical Properties Associated With Genotoximentioning
confidence: 99%
“…CNTs, in addition to Dynamic Light Scattering, were also characterized by transmission electron microscopy and EDX analysis, as described earlier [15]. Diameters as determined by TEM were similar to what was indicated by the producer.…”
Section: Resultsmentioning
confidence: 82%
“…CNTs suspended in DMEM +10% fetal bovine serum have been characterized physicochemically by Dynamic Light Scattering and Laser Doppler Velocimetry (Nanosizer, determination of size and surface charge), transmission electron microscopy (FEI Tecnai G² 20, determination of size), and energy dispersive X-ray spectroscopy (FEI Tecnai G² 20 with Standard SUTW detector, detection of metal contamination) as described in a previous study [15]. Heavy metal contamination was shown to be below detection threshold.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation